Pengaruh Content Marketing Dan Kelengkapan Produk Terhadap Keputusan Pembelian Di Holly Mart Bima - Dhea Auliya; Ismunandar Ismunandar; Feni Aryani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of content marketing and product completeness on consumer purchasing decisions at Holly Mart Bima. The development of digital technology has encouraged businesses to utilize social media and online platforms as effective marketing strategies, including content marketing. Additionally, product completeness in retail stores is one of the key factors influencing consumer interest and purchasing decisions. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to Holly Mart Bima consumers and analyzed using multiple linear regression to examine the simultaneous and partial effects of the two independent variables on the dependent variable. The results show that content marketing and product completeness simultaneously have a significant effect on purchasing decisions. Partially, each variable also has a positive and significant impact on consumer purchasing decisions. These findings indicate that engaging content marketing strategies and comprehensive product availability can enhance consumer appeal and drive purchases. Therefore, it is recommended that Holly Mart’s management continue to optimize both aspects to increase customer loyalty and sales volume.